Load-switching strategy for voltage balancing of bipolar DC distribution networks based on optimal automatic commutation algorithm - Liao, Jianquan (2022)
The unbalanced DC loads between the positive and negative poles of bipolar DC distribution network leads to the increase of unbalanced current (voltage) and power losses. This affects the efficiency of DC power transmission and also influences the power quality of the DC load. In this article, an unbalanced DC load switching strategy based on automatic commutation switch (ACS) and genetic algorithm (GA) is proposed. The proposed method can automatically adjust the power supply polarity (PSP) of the DC load according to the unbalanced currents in the bipolar network. This article also introduces the configuration and topology of ACS in a bipolar DC distribution network. Furthermore, the ACS and its control diagrams are designed. The state of ACS is represented by the switch state vector, which corresponds to the gene sequence in the GA. Consequently, the calculation algorithm of switch commutation command (SCC) based on the vector gene coding strategy is proposed. In accordance with the optimal SSC, an online unbalanced-load switching strategy is designed. Finally, the simulation is built in MATLAB/Simulink to verify the effectiveness of the proposed method.